BANKRUPTCY PREDICTION USING ZAVGREN MODEL (A Study on Automotive and Spare Part Companies Listed in the Indonesia Stock Exchange in the Period of 2012-2016) - ADRIYAN, RIZKY (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to predict and determine bankruptcy of automotive and spare part companies listed in the Indonesia Stock Exchange (IDX) in the period of 2012-2016 using Zavgren model. The financial ratios in this study, i.e. the independent variables, are inventory, receivable, cash, quick, return on investment, debt, and turn. This quantitative descriptive research provides an objective description about a situation using statistical procedures or other ways of quantification.This study uses a sample of 45 respondents selected through saturated sampling technique from the population of automotive and spare part companies. Logistic regression was used to analyze the data, and cut-off was used to distinguish between healthy, vulnerable, and bankrupt condition to help determine the financial level of the companies,.The results of this study indicate that the independent variables in Zavgren model consisting of inventory, receivable, cash, quick, return on investment, debt, and turn are able to explain the dependent variable and have a simultaneous effect on bankruptcy. In addition, inventory is partially the most significant variable for bankruptcy. Furthermore, 2 companies are categorized as healthy, 5 companies are categorized as vulnerable, and 2 companies are declared bankrupt.